Propagation effects in multipass high harmonic generation from plasma surfaces. (16th September 2020) - Tietze, S; Zepf, M; Rykovanov, S G; Yeung, M
Abstract: Multipass high harmonic generation from plasma surfaces is a promising technique to enhance the efficiency of the generation process. In this paper it is shown that there is an optimal distance between two targets where the efficiency is maximized, depending on the laser and plasma parameters. This can be explained by the Gouy phase shift, which leads to the relative phase between the colours being changed with propagation in free space. A simple model is used to mimic the propagation of light from one target to another and to observe this effect in 1D particle-in-cell (PIC) simulations. The results are also verified using 2D PIC simulations.